2020
DOI: 10.3390/atmos11050474
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Trace Metal Deposition from Natural and Anthropogenic Sources in Western Australia

Abstract: Aerosols from Western Australia supply micronutrient trace elements including Fe into the western shelf of Australia and further afield into the Southern and Indian Oceans. However, regional observations of atmospheric trace metal deposition are limited. Here, we applied a series of leaching experiments followed by total analysis of bulk aerosol samples to a unique time-series of aerosol samples collected in Western Australia to determine atmospheric concentrations and solubilities of Fe and V, Mn, Co, Zn, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 72 publications
(120 reference statements)
2
13
0
Order By: Relevance
“…Additionally, the complex ion formation mechanisms inherent to LDI may favor the formation of other ions (e.g., K: m/z = +39, + 41) over the formation of the above-mentioned elemental ions. Mass spectra of ambient tropospheric particles associated with biomass-burning influenced air masses appear to contain signatures for Zn 67 based on the characteristic isotope pattern of 64 Zn, 66 Zn, and 68 Zn, which is consistent with bulk measurements of BBA-impacted air that observe Zn concentrations to be highly enhanced above background levels. 16,18 These mass spectra also contained signatures that could arise from Fe, 67 one of the elements commonly seen in the particles we examined here and in past work.…”
Section: ■ Results and Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Additionally, the complex ion formation mechanisms inherent to LDI may favor the formation of other ions (e.g., K: m/z = +39, + 41) over the formation of the above-mentioned elemental ions. Mass spectra of ambient tropospheric particles associated with biomass-burning influenced air masses appear to contain signatures for Zn 67 based on the characteristic isotope pattern of 64 Zn, 66 Zn, and 68 Zn, which is consistent with bulk measurements of BBA-impacted air that observe Zn concentrations to be highly enhanced above background levels. 16,18 These mass spectra also contained signatures that could arise from Fe, 67 one of the elements commonly seen in the particles we examined here and in past work.…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…For example, analyses of iron solubility in volcanic ashes have shown that iron is released more quickly from amorphous glasses than from crystalline phases. ,, If some of the iron and phosphorus in BBA exists in amorphous or poorly crystalline phases, as in the particle in Figure a, then these phases could explain the relatively high observed solubility of iron and phosphorus in BBA. Prior work with coal combustion aerosol shows that fly ash particles generated from partially combusted material release greater amounts of iron during dissolution than more completely combusted particles, potentially due to a higher fraction of more soluble Fe 2+ phases. , If many of the mineral BBA particles we observe result from partially combusted material, as we suggest above, then this would support the idea that these particles contribute to the high concentration of soluble Fe and P often observed in BBA. ,,, However, as the particle in Figure b demonstrates, it is also possible to produce well-formed crystalline phases during biomass combustion. Particles like the one in Figure b, which appears to be composed of a crystalline iron oxide, are more likely to be insoluble and contain little bioavailable iron.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…aerosol samples (Bowie et al, 2009;Perron et al, 2020;Strzelec et al, 2020) provide key information about the transport and geochemistry of aeolian TEs, these samples only integrate atmospheric measurements over a few days (Anderson et al, 2016). Moreover, the short time scale of oceanographic campaigns (several weeks) does not allow for an accurate representation of either highly episodic major weather events (dust and fire emissions) or seasonal and inter-annual variability in dust deposition trends (Jickells & Moore, 2015;Mahowald et al, 2009).…”
mentioning
confidence: 99%
“…At the same time, the discharges from the increased chemical processes, agricultural processes, and energy conversions, amongst other applications, have elevated water pollution. These anthropogenic processes have been observed to be the major contributors to the elevated concentrations of trace metals in water bodies [ 2 , 3 , 4 , 5 , 6 ]. The statistics published by the World Health Organization (WHO), based on the 2017 figures, pronounce that 785 million people lack basic drinking-water services, including 144 million people who are dependent on surface water.…”
Section: Introductionmentioning
confidence: 99%